2021
DOI: 10.1515/fjsb-2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

Ambitionierte Klimapolitik von unten – Möglichkeiten und Hürden zivilgesellschaftlicher Beteiligung an der Ausarbeitung von Klimazielen und ihrer Umsetzung

Abstract: Zusammenfassung Ambitionierter Klimaschutz ist eine gesamtgesellschaftliche, komplexe Herausforderung und Gestaltungsaufgabe, die das Zusammenspiel unterschiedlichster Akteur*innen bedarf. Zivilgesellschaftlichen Organisationen kommt bei der Ausgestaltung von notwendigen klimapolitischen Rahmenbedingungen und deren Umsetzung eine entscheidende Rolle zu. Sie sind konstruktive, treibende Kraft im Transformationsprozess und bringen dabei die Bedürfnisse und Interessen von Menschen von vor Ort in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Divergent perceptions of the role of civil society in such processes have also been noted by the Independent Institute for Environmental Issues, which has discussed government perceptions on the purpose of participation in three countries. 45 Oxfam's current research also revealed a perception among some in one government that their NDC reflected pre-existing government climate commitments and policy frameworks that had previously been developed with community needs in mind or with civil society input. Thus, participation by civil society in the NDC process itself, and possibly in NDC implementation or monitoring, was not seen as necessary.…”
Section: Who Was Not Involved?mentioning
confidence: 86%
“…Divergent perceptions of the role of civil society in such processes have also been noted by the Independent Institute for Environmental Issues, which has discussed government perceptions on the purpose of participation in three countries. 45 Oxfam's current research also revealed a perception among some in one government that their NDC reflected pre-existing government climate commitments and policy frameworks that had previously been developed with community needs in mind or with civil society input. Thus, participation by civil society in the NDC process itself, and possibly in NDC implementation or monitoring, was not seen as necessary.…”
Section: Who Was Not Involved?mentioning
confidence: 86%